Peningkatan Kualitas Layanan dan Efisiensi Waktu Dalam Proses Pengecatan Kuku : Studi Pada Usaha Pengecatan Kuku (Nail Painting) di Industri Jasa Kecantikan - Angelita Lavenia; Claudia Raberta Repanela; Dewi Lestari; Puja Astuti (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This research aims to analyze the level of consumer satisfaction with service quality in the beauty services industry, especially in the nail painting business. The factors that are the focus of the research are improving service quality and time efficiency in the nail painting process. The research method used is qualitative with data collection techniques in the form of observation, interviews and documentation. The research results show that Angelnailartpky business owners have made various efforts to improve service quality and time efficiency, such as monitoring work, updating knowledge, and receiving input from consumers. Improving service quality and time efficiency is expected to increase consumer satisfaction and business profitability. The advice given is that Angelnailartpky continues to increase consumer satisfaction and strengthen its position in the beauty services market.